Mycobacterium tuberculosishypoxic response protein 1 (Hrp1) augments the pro‐inflammatory response and enhances the survival ofMycobacterium smegmatisin murine macrophages. Issue 7 (July 2017) - Sun, Changfeng; Yang, Guoping; Yuan, Jinning; Peng, Xuan; Zhang, Chunxi; Zhai, Xiaoqian; Luo, Tao; Bao, Lang
Abstract : Purpose. : The DosR/DosS two‐component regulatory system of Mycobacterium tuberculosis regulates the expression of numerous genes under stress conditions and is important for the long‐term survival of M. tuberculosis in the host. The rv2626c gene of M. tuberculosis is one of the most strongly induced transcripts of the dormancy regulon. This study focused on the immunological effects and possible function of Rv2626c in maintaining mycobacterial survival under various stress conditions. Methodology. : We heterologously expressed the Rv2626c protein in Mycobacterium smegmatis by constructing a recombinant strain Ms_rv2626c. The viability of Ms_rv2626c was evaluated both in vivo and ex vivo . Different stress conditions, including acidified sodium nitrite, malachite green, low pH, SDS and lysozyme, were used to evaluate the effect of Rv2626c on bacterial resistance. An in vitro assay using a macrophage infection model was utilized to investigate the potential effect of Rv2626c to alter the immune response of host cell and its associated pathways. The effect of Rv2626c on cell necrosis was also explored. Results. : The expression of Rv2626c‐enhanced M. smegmatis survival under hypoxia and nitric oxide stress in vitro, and this enhancement was maintained within macrophages and in mouse tissues. In addition, macrophages infected with M. smegmatis expressing Rv2626c showed significantly higher interleukin‐1β (IL‐1β), IL‐6, tumour necrosis factor‐α (TNF‐α) and inducible nitric oxide synthase (iNOS) expression, as well as a higher level of cell necrosis, compared with the control. Conclusion. : M. tuberculosis protein Rv2626c plays a significant role in stimulating macrophages to provoke a pro‐inflammatory response and in mycobacterial survival during infection.